A Case of Milky Urine Due to Chyluria - Arif, NUM; Biswas, R; Zaman, W (Bangladesh Medical Journal, 2014)
Chyluria is an uncommon condition characterized by lymphatic fluid excretion into the urinary tract. Most common cause of chyluria is the infection by parasites e.g. filariasis. Medical treatment is often insufficient to treat the cases of chronic chyluria for which the standard treatment is surgical renal pedicle lymphatic disconnection. However, sclerotherapy by instillation of a sclerosant agent into the renal pelvis may represent an alternative to surgery. This technique has the advantage of being less invasive. We are presenting two cases, presented to us with the complaint of milky urine for more than 3 years. All tests for infectious diseases remained negative. Chyluria was confirmed by urinary chyle test and urinary triglyceride. Cystoscopy showed a clear diagnosis of a milky urine jet from ureteric orifice. Retrograde pyelography revealed pyelolymphatic fistula in one case. Patients were treated successfully with renal pelvic instillation of diluted povidone iodine(0.2%). solution and non-ionic contrast(omnipac). We used sclerotherapy with povidone iodine solution as a safe, effective and minimally invasive treatment in our patient with chyluria. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18812 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 59-60